SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PRIORITAS PERBAIKAN JALAN MENGGUNAKAN METODE GAP - Nurahman Nurahman; Andry Wardana (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Roads are very important infrastructure for economic growth in each region because roads are a means of connecting one place to another. all information related to damaged roads is recorded and collected by the public works and spatial planning offices to be managed. but from all the damaged road data, the responsible agency is sometimes wrong to determine the priority order of roads that will be repaired first so that it is not on target. Therefore, in this study a decision support system for determining the priority of road repair using the gap method was built which is expected to help the public works and spatial planning offices in determining which road priorities will be repaired first based on the criteria of road condition, daily traffic, road surface type, road length and road width. based on the results of the calculation that became the first rank or top priority to be repaired was JLM002 (Mt.Haryono Barat) which obtained the highest value of 4.4. Therefore, the road deserves to be a priority to get repairs and handling first.